Madelung’s Disease: Is Insobriety the Chief Cause? - Gao, Yuan; Hu, Ji-lin; Zhang, Xian-xiang; Zhang, Mao-shen; Lu, Yun (Aesthetic plastic surgery, 2017)
Background Madelung’s disease (MD) is a rare disease of unknown etiology that is characterized by massive fatty deposits distributed in a symmetrical pattern mainly in the head, neck, and upper trunk. Here, we sought to explore the pathogeny and treatment of MD. Methods We enrolled ten patients who underwent surgical operations and one patient who refused an operation at our hospital between January 2009 and December 2016. We collected their medical histories and the preoperative and postoperative serological indices. The serum chemistry clinical outcomes were compared between the preoperative and postoperative states. Results The mean alcohol intake of the eleven patients exceeded 450 g daily. Ten patients underwent open excisions, and the other patient refused an operation. No significant differences were observed between the preoperative and postoperative serum chemistry results. No recurrence has yet been observed in any of the ten operated patients. Conclusions All of the patients in our study had associated alcoholism. Thus, insobriety might be one of the causes of MD. We believe that open operations may be an effective treatment based on the outcomes of the surgeries. Level of Evidence IV This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .